Risk factors for Mycobacterium tuberculosis infection among children in Greenland - Bolette Søborg; Aase Bengaard Andersen; Mads Melbye; Jan Wohlfahrt; Mikael Andersson; Robert J Biggar; Karin Ladefoged; Vibeke Ostergaard Thomsen; Anders Koch (The World Health Organization, 2011)
OBJECTIVE: To examine the risk factors for Mycobacterium tuberculosis infection (MTI) among Greenlandic children for the purpose of identifying those at highest risk of infection. METHODS: Between 2005 and 2007, 1797 Greenlandic schoolchildren in five different areas were tested for MTI with an interferon gamma release assay (IGRA) and a tuberculin skin test (TST). Parents or guardians were surveyed using a standardized self-administered questionnaire to obtain data on crowding in the household, parents' educational level and the child's health status. Demographic data for each child - i.e. parents' place of birth, number of siblings, distance between siblings (next younger and next older), birth order and mother's age when the child was born - were also extracted from a public registry. Logistic regression was used to check for associations between these variables and MTI, and all results were expressed as odds ratios (ORs) and 95% confidence intervals (CIs). Children were considered to have MTI if they tested positive on both the IGRA assay and the TST. FINDINGS: The overall prevalence of MTI was 8.5% (152/1797). MTI was diagnosed in 26.7% of the children with a known TB contact, as opposed to 6.4% of the children without such contact. Overall, the MTI rate was higher among Inuit children (OR:4.22; 95% CI: 1.55-11.5) and among children born less than one year after the birth of the next older sibling (OR:2.48; 95% CI: 1.33-4.63). Self-reported TB contact modified the profile to include household crowding and low mother's education. Children who had an older MTI-positive sibling were much more likely to test positive for MTI themselves (OR:14.2; 95% CI: 5.75-35.0) than children without an infected older sibling. CONCLUSION: Ethnicity, sibling relations, number of household residents and maternal level of education are factors associated with the risk of TB infection among children in Greenland. The strong household clustering of MTI suggests that family sources of exposure are important.